FPGA Implementation of Precision Time Protocol and Its Performance Analysis Under Traffic Load - Yabacioglu, Muhammed Emin; Demir, M. Selim; Hokelek, Ibrahim; Engin, Seref Naci (IEEE, 2021)
Applications running in a distributed network architecture such as industrial automation, Internet of Things (IoT), and avionics systems need time synchronization. IEEE 1588 precision time protocol (PTP), which has been heavily used in these applications, can provide nanosecond-level time synchronization. The time synchronization accuracy can be significantly improved if the time-stamping process is implemented closer to the physical layer. In this paper, the IEEE 1588 protocol has been implemented on Field Programmable Gate Arrays (FPGA) and its performance analysis under various traffic loads are carried out. The experiment results show that the nanosecond-level time synchronization is sustainable when the traffic congestion in the network is low. However, it is observed that the asymmetric path delay in the network adversely affects the synchronization accuracy.
Keywords: Precision Time Protocol (PTP); FPGA; time synchronization; asymmetric path delay; Engineering; Telecommunications